Augmentation of gas turbine performance using integrated EAHE and Fogging Inlet Air Cooling System. (15th December 2019) - Barakat, S.; Ramzy, Ahmed; Hamed, A.M.; El-Emam, S.H.
Abstract: In the present work, new hybrid cooling system is demonstrated and compared with other configurations of gas turbine inlet air-cooling systems. The cooling configurations include the earth-air heat exchanger, fogging and a new hybrid cooling system. Three models are developed, the first is for prediction of the cooling potential of the fogging system and the second is based on the transient one-dimensional heat transfer modeling which is used to describe the thermal behavior of the earth-air heat exchanger. The third model is a combination of earth-air heat exchanger and fogging cooling system as a new hybrid cooling system. New Damietta power plant located in the coastal region in Egypt (Latitude = 31.4 and Longitude = 31.7) is applied as a case study. A comparison between the effects of the three air cooling techniques on the gas turbine performance was performed. It is observed that the hybrid system is superior to the unitary systems as it is capable of boosting the average annual energy by 9.8% versus 8 and 6.6% for fogging and earth-air heat exchanger system; respectively. In addition, the hybrid system reduces the water consumption by 50% compared to the fogging system. Moreover, the hybrid cooling system is the most efficient method in the areas where the temperature is over 30 °C and the relative humidity is less than 60%. Highlights: Hybrid cooling is superior for a temperature above 30 °C and humidity less than 60%. For a temperature exceeds 30 °C and humidity over 60%, the EAHE is the best choice. Fogging is superior if the temperature is under 30 °C and humidity is under 60%. The water consumption diminished by about 50% using the hybrid cooling of GT.